TAX BURDEN OF THE ENTERPRISES OF THE REAL SECTOR OF ECONOMY IN THE RUSSIAN FEDERATION - N. Beskorovaynaya; N. Marchenko (Вестник Северо-Кавказского федерального университета)
The analysis of tax burden of the real sector of economy and the organizations of the processing productions in the Russian Federation on various bases of comparison is carried out. The increased volume of tax and insurance payments (in relation to results of economic activity) in the industry is caused by functioning mainly of the medium-sized and large enterprises applying the general system of taxation with the big specific weight of indirect taxes and income tax. However comparison of obligatory payments to size of the invested capital allows to receive a smaller variation of values of tax burden on branches of economy. Conclusions about dependence of tax burden of the enterprises on influence of market factors and need of preservation of equal conditions of taxation for different types of economic activity are proved.